2020
DOI: 10.1021/acs.orglett.0c02672
|View full text |Cite
|
Sign up to set email alerts
|

CuI/2-Aminopyridine 1-Oxide Catalyzed Amination of Aryl Chlorides with Aliphatic Amines

Abstract: A class of 2-aminopyridine 1-oxides are discovered to be effective ligands for the Cu-catalyzed amination of less reactive (hetero)­aryl chlorides. A wide range of functionalized (hetero)­aryl chlorides reacted with various aliphatic amines to afford the desired products in good to excellent yields under the catalyst of CuI/2-aminopyridine 1-oxides. Furthermore, the catalyst system worked well for the coupling of cyclic secondary amines and N-methyl benzylamine with (hetero)­aryl chlorides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 120 publications
0
18
0
Order By: Relevance
“…A limitation of Cu-catalyzed C–N cross-coupling reactions is their lower efficiency toward less reactive aryl chloride substrates. This limitation was addressed with the introduction of an oxalic diamide ligand scaffold by Ma et al Recently, a new class of 2-aminopyridine-1-oxide ligands was disclosed by Liu and co-workers as effective ligands for the Ullman coupling of aryl chlorides . A variety of aryl and heteroaryl chlorides were coupled with an assortment of primary and cyclic secondary amines in moderate to excellent yields (Scheme ).…”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A limitation of Cu-catalyzed C–N cross-coupling reactions is their lower efficiency toward less reactive aryl chloride substrates. This limitation was addressed with the introduction of an oxalic diamide ligand scaffold by Ma et al Recently, a new class of 2-aminopyridine-1-oxide ligands was disclosed by Liu and co-workers as effective ligands for the Ullman coupling of aryl chlorides . A variety of aryl and heteroaryl chlorides were coupled with an assortment of primary and cyclic secondary amines in moderate to excellent yields (Scheme ).…”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…This limitation was addressed with the introduction of an oxalic diamide ligand scaffold by Ma et al 56 Recently, a new class of 2-aminopyridine-1-oxide ligands was disclosed by Liu and co-workers as effective ligands for the Ullman coupling of aryl chlorides. 57 A variety of aryl and heteroaryl chlorides were coupled with an assortment of primary and cyclic secondary amines in moderate to excellent yields (Scheme 38). However, incomplete conversion of the aryl chloride was observed with more sterically hindered acyclic secondary amines and morpholine.…”
Section: ■ Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering work of Ullmann and Goldberg that introduced copper for the arylation of amines/amides using an aryl iodide to form a C­(sp 2 )–N bond is captivating. Heteroatom-arylated compounds containing C–heteroatom bonds (C–N, C–S, and C–O) are important for the synthesis of agrochemicals, pharmaceuticals, and biologically active compounds. However, the conventional methods to form such bonds use pre-functionalized reactants and also produce an significant amount of hazardous waste . Migita et al reported the use of a palladium catalyst for the reaction between an aryl halide and aminostannate to form a C­(sp 2 )–N bond.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-catalyzed amination can smoothly occur by using some O, O; N, O; and N, N ancillary ligands. 3 Although these ligands can adequately accelerate the coupling reaction, they are difficult to recycle and reuse, and large-scale production is costly, especially for some expensive ligands and complexes formed by ligand–copper( i ) or ( ii ). 4 Therefore, it is necessary to develop copper-catalyzed Ullmann coupling reaction ligands with recyclability and practical application value, although some recyclable ligands have been reported.…”
mentioning
confidence: 99%